ANTHROPOMETRIC PROFILE OF GYMNASTS PARTICIPATING IN THE EUROPEAN GAMES 2015 IN BAKU, AZERBAIJAN - Maria-Raquel G. Silva; Hugo-Henrique Silva; Teresa Luemba (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
Sports performance is strongly influenced by the athletes' anthropometric profile. In the specific case of Gymnastics, body weight assumes particular relevance, given the aesthetic character of this sport. Anthropometric data were collected from 309 gymnasts (20.9 ± 4.1 years old) participating in the 2015 European Games: age, body weight and height, from a database of the organization of this competition available online in the 5 disciplines of the Gymnastics included in the competition, namely Men´s and Women´s Artistic Gymnastics, Rhythmic Gymnastics, Acrobatic Gymnastics and Aerobic. Body mass index was calculated. Female gymnasts were significantly younger and lighter than male gymnasts and had a lower body mass index than males (P = 0.000). Female athletes were in the 25th percentile for weight and BMI and in the 15th percentile for height, according to their age. Male gymnasts were in the 25th percentile for weight, height and BMI. Female acrobatic gymnasts were younger and lighter (25th percentile) than other gymnastics disciplines; rhythmic gymnasts presented the lowest BMI (5th percentile). Male artistic gymnasts were the lightest (15th percentile) and with the lowest BMI (25th percentile) within the male participants. BMI was dependent on weight, height and gender, with exception for exclusive-gender disciplines and, surprisingly, also in Aerobics. Gymnasts presented an anthropometric profile with results for body weight, height and body mass index below the normal for their age.